A first principles study of convection cells to shear flow instability in 2D Yukawa liquids driven by Reynolds stress - Pawandeep Kaur; Rajaraman Ganesh (Scientific Reports)
Abstract The stability of kinetic-level convection cells (wherein the magnitude of macroscopic and microscopic velocities are of same order) is studied in a two-dimensional Yukawa liquid under the effect of microscopic velocity perturbations. Our numerical experiments demonstrate that for a given system aspect ratio $$β$$ viz., the ratio of system length $$L_x$$ to its height $$L_y$$ and number of convective rolls initiated $$N_c$$ , the fate of the convective cells is decided by $$β _c = β /N_c$$ . For $$β _c < 1$$ , Reynolds stress is found to be self-consistently generated and sustained, which results in tilting of convection cells, eventually leading to shear flow generation, whereas for $$β _c \ge 1$$ , parallel shear flow is found to be untenable. An unambiguous quantitative connection between Reynolds stress and the onset of shear flow using particle-level data is established without free parameters. The growth rate of the instability, the role of frictional forces, generalization of our findings and the possibility of realizing the same in experiments are also discussed.